Dimensions humaine et sociale du développement durable : une problématique séparée du volet environnemental ? - Sandrine Rousseau (Développement Durable et Territoires)
The implementation of sustainable development policies on a global scale should icrease the coherence of the management of environmental and labour resources in the various countries. This paper aims at explaining the consequences of the different forms of management and organisation implemented recently. It compares two indicators, poverty rates (and decent labour) and the ecological footprint, in order to suggest policies that should be led in OECD countries to achieve sustainable development. Several scenarios are identified, from the countries that show a high poverty rate and a strong environmental print to other countries that are more concerned by both environmental and labour resources. This paper attempts to present the features that can explain the variety of configurations.